Education on Sugar-Sweetened Beverage (SSB) for increasing knowledge mothers in Pattallassang Village - Karini, Tri Addya; Kurniati, Yessy; Wijaya, Dian Rezki; Aswadi, Aswadi; Nurhidayat, Nurhidayat; Asgari, Muhammad Hidir (SAMATA JOURNAL OF PUBLIC HEALTH SCIENCE, 2025)
Excessive consumption of Sugar-Sweetened Beverage (SSB) can cause various health problems, such as weight gain, diabetes and disease. The approach used in this service is Participatory Action Research (PAR), which means looking at the level of participation of participants in outreach and demonstration activities. In this approach, the community service team carries out persuasive and non-commanding facilitation efforts which aim to increase community knowledge, attitudes and behavior in finding, planning and solving problems using the resources/potential they have including the participation and support of community leaders. This community service activity uses an outreach method with a lecture, question and answer and discussion approach. The activity participants were mothers in Pattallassang Village. Before and after education, participants were given a questionnaire to determine their level of knowledge about MBDK. The results of community service show that there is an increase in the knowledge of mothers in Pattallassang Village before and after education about MBDK, with p value = 0.008. Outreach activities about MBDK to mothers in Pattallassang Village have succeeded in increasing their knowledge significantly.